The heritage of muslim culture in the history of Lithuania and Poland - Marat Zufarovich Galiullin, Yakov Yakovlevich Grishin, Denis Radievich Sharafutdinov, (Opción, 2019)
The article discusses the main elements of the heritage of the Muslim culture in Eastern Europe. The study is based on a solid source and historiographic base. As a result, the appearance of the Tatars in the territory of Lithuanian principality, later Pzecz Pospolita, was due to the political processes that took place in Eastern Europe at the turn of the XIII- XIV centuries. In conclusion, speaking of the heritage of Muslim culture in the history of Lithuania and Poland, it is necessary to refer to architectural monuments (wooden mosques), customs and traditions that the Lithuanian Tatars sought to preserve.